Comparison of Solubility and Water Sorption of Two Different Soft Lining Denture MaterialsCOMPARISON OF SOLUBILITY AND WATER SORPTION OF TWO DIFFERENT SOFT LINING MATERIAL - Das, Gotam; Khokhar, Maimuna; Naeem, Sajid; Baloch, Reehana (Journal of Ayub Medical College Abbottabad, 2018)
Background: Soft denture lining materials play a very important role in Removable Prosthodontics because of their ability to provide a cushioning effect for maintaining the health of traumatized, swollen and deformed mucosa through absorption and equal redistribution of stresses over the entire area covered by denture, thus eliminating the distortion of oral mucosa. The objective of this investigation is to quantify and relate the mean solubility and water sorption of acrylic resin based permanent soft liner with a silicone based permanent soft liner. Method: Two different permanent soft denture liners, i.e., acrylic and silicone based are selected for this study, 30 samples of each material are prepared in the form of circular disks of the 30 disks, and three subgroups of ten disks each are made for the two materials. Initially the processed disks will be weighed 3 times daily with an analytical balance until a constant weight is achieved. This initial weight of each specimen is denoted by W1. Each subgroup of 10 specimens is immersed in 250ml of 37 °C distilled water in a sealed polyethylene container. First subgroup is tested after 1 week, second after 4 weeks and third after 6 weeks of immersion. Results: Ever soft has higher solubility (1.67mg/cm2 ±0.26 mg/cm2laboratory-processed) and sorption (0.84 mg/cm2 ±0.35 mg/cm2laboratory-processed) than Molloplast B (0.40 mg/cm2 ±0.08 mg/cm2solubility and 0.27 mg/cm2 ±0.16 mg/cm2 sorption) after 6 weeks of immersion. Conclusion: It is therefore concluded that Molloplast B may provide better clinical success based on its lower solubility and water sorption. Keywords: Soft denture liner; Water sorption; Solubility